Treatment with AICAR inhibits blastocyst development, trophectoderm differentiation and tight junction formation and function in mice - Calder, Michele D; Edwards, Nicole A; Betts, Dean H; Watson, Andrew J (Molecular human reproduction, 2017)
What is the impact of adenosine monophosphate-activated protein kinase (AMPK) activation on blastocyst formation, gene expression, and tight junction formation and function? AMPK activity must be tightly controlled for normal preimplantation development and blastocyst formation to occur. AMPK isoforms are detectable in oocytes, cumulus cells and preimplantation embryos. Cultured embryos are subject to many stresses that can activate AMPK. Two primary experiments were carried out to determine the effect of AICAR treatment on embryo development and maintenance of the blastocoel cavity. Embryos were recovered from superovulated mice. First, 2-cell embryos were treated with a concentration series (0-2000 μM) of AICAR for 48 h until blastocyst formation would normally occur. In the second experiment, expanded mouse blastocysts were treated for 9 h with 1000 μM AICAR. Outcomes measured included development to the blastocyst stage, cell number, blastocyst volume, AMPK phosphorylation, Cdx2 and blastocyst formation gene family expression (mRNAs and protein measured using quantitative RT-PCR, immunoblotting, immunofluorescence), tight junction function (FITC dextran dye uptake assay), and blastocyst ATP levels. The reversibility of AICAR treatment was assessed using Compound C (CC), a well-known inhibitor of AMPK, alone or in combination with AICAR. Prolonged treatment with AICAR from the 2-cell stage onward decreases blastocyst formation, reduces total cell number, embryo diameter, leads to loss of trophectoderm cell contacts and membrane zona occludens-1 staining, and increased nuclear condensation. Treatment with CC alone inhibited blastocyst development only at concentrations that are higher than normally used. AICAR treated embryos displayed altered mRNA and protein levels of blastocyst formation genes. Treatment of blastocysts with AICAR for 9 h induced blastocyst collapse, altered blastocyst formation gene expression, increased tight junction permeability and decreased CDX2. Treated blastocysts displayed three phenotypes: those that were unaffected by treatment, those in which treatment was reversible, and those in which effects were irreversible. Not applicable. Our study investigates the effects of AICAR treatment on early development. While AICAR does increase AMPK activity and this is demonstrated in our study, AICAR is not a natural regulator of AMPK activity and some outcomes may result from off target non-AMPK AICAR regulated events. To support our results, blastocyst developmental outcomes were confirmed with two other well-known small molecule activators of AMPK, metformin and phenformin. Metformin, an AMPK activator, is widely used to treat type II diabetes and polycystic ovarian disorder (PCOS). Our results indicate that early embryonic AMPK levels must be tightly regulated to ensure normal preimplantation development. Thus, use of metformin should be carefully considered during preimplantation and early post-embryo transfer phases of fertility treatment cycles. Canadian Institutes of Health Research (CIHR) operating funds. There are no competing interests.